Thicker than blood - Omer, Mike (Omer, Mike. Zoe Bentley, 2020)
"A murderer who drinks his victim's blood? FBI profiler Zoe Bentley and Agent Tatum Gray thought they'd seen it all, but this young woman's barbaric murder is especially hard to stomach. They didn't expect to work this case. But vampirism aside, the murderer's MO is identical to that of Rod Glover - the serial killer who's been pursuing Zoe since childhood. Forensics reveals the murder to be his work, but not his alone; desperate to fulfill his sick purpose, he has taken on an equally depraved partner.Zoe's own frustration grows after another woman turns up dead and drained - and another goes missing. Time is running out: Zoe knows her own death will be the climax of Glover's sinister play, which has been unfolding for twenty years. To stop Glover and his vile partner, she'll need to plunge deep into their motives; but this means drawing ever closer to becoming another casualty of a dark, dark thirst."--Publisher description.